1996
DOI: 10.1007/bf02247440
|View full text |Cite
|
Sign up to set email alerts
|

α2-Adrenoceptor antagonists potentiate acetylcholinesterase inhibitor effects on passive avoidance learning in the rat

Abstract: The cholinergic hypothesis of Alzheimer's disease (AD) has strongly influenced research on learning and memory over the last decade. However, there has been limited success treating AD dementia with cholinomimetics. Furthermore, there are indications that other neurotransmitter systems affected by this disease may be involved in cognitive processes. Animal studies have suggested that norepinephrine and acetylcholine may interact in learning and memory. The current experiments investigate this interaction in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…Although, as previously mentioned, no studies have been found in which to be administered namely these 3 agonists in various combinations, there are studies that combine all three neurosystems [8,15], the results being similar and confirming those obtained by us. We especially should remind the study by Camacho et al [15], which used over 20 cholinergic and catecholaminergic agonists known at that time.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Although, as previously mentioned, no studies have been found in which to be administered namely these 3 agonists in various combinations, there are studies that combine all three neurosystems [8,15], the results being similar and confirming those obtained by us. We especially should remind the study by Camacho et al [15], which used over 20 cholinergic and catecholaminergic agonists known at that time.…”
Section: Discussionsupporting
confidence: 85%
“…We especially should remind the study by Camacho et al [15], which used over 20 cholinergic and catecholaminergic agonists known at that time. The study did not, however, include pergolide, which began to be used for the various cognitive behavioral tests starting from the year of 2000.…”
Section: Discussionmentioning
confidence: 99%
“…In the object recognition task, administration of tacrine before the learning trial has recently been found to improve the memory performance (Moser et al 2002). The same tacrine treatment was also effective in the passive avoidance task (Camacho et al 1996), while administration immediately after the learning trial had no effect on the retention performance . These results of tacrine are in agreement with our metrifonate and donepezil data.…”
Section: Ache Inhibition and Object Recognition Memorymentioning
confidence: 97%
“…Dosages were chosen to ensure sufficient inhibition of ChE (and in case of galantamine, significant APL activity), and clinical relevance compared to human dosages based on dosage per kg of bodyweight and plasma levels (Fishkin et al 1993;Camacho et al 1996;Misztal et al 1996;Wang and Tang 1998;Bejar et al 1999). …”
Section: Drug Treatmentmentioning
confidence: 99%